Embedding Aboriginal cultural governance, capacity, perspectives and leadership into a local Public Health Unit Incident Command System during COVID-19 in New South Wales, Australia - Kirsty Hope; David N Durrheim; Kristy Crooks; Kylie Taylor; Charlee Law; Katie Brett; Peter Murray; Julie Kohlhagen (BMJ Global Health, 2023)
This case study describes the development and implementation of a governance structure that prioritised First Nations peoples in a local public health Incident Command System activated for the COVID-19 pandemic response in New South Wales, Australia. Using lessons learnt from past pandemics and planning exercises, public health leaders embedded an approach whereby First Nations peoples determined and led community and culturally informed pandemic control strategies and actions.In March 2020, First Nations governance was embedded into the local public health emergency response to COVID-19 in the Hunter New England region of New South Wales, Australia, enabling First Nations staff and community members to actively participate in strategic and operational decision-making with the objective of minimising COVID-19-related risks to First Nations peoples and communities. The model provided cultural insight and oversight to the local COVID-19 response; strengthened and advanced First Nations leadership; increased the First Nations public health workforce; led the development of First Nations disease surveillance strategies; and supported working groups to appropriately respond to local needs and priorities. This model demonstrates the feasibility of reframing a standard Incident Command System to embed and value First Nations principles of self-determination and empowerment to appropriately plan and respond to public health emergencies.